LEISURE-TIME PHYSICAL INACTIVITY IN UNDERGRADUATE STUDENTS OF PHYSICAL EDUCATION FROM BAHIA, BRAZIL - Franco, Dayana Chaves; Sousa, Thiago Ferreira de (Journal of Health Care, 2017)
Introduction: Physical inactivity is one of the main risk factors related to worldwide mortality, with great implications for chronic diseases. In relation to university students, physical inactivity represents a prevalent behavior. Objective: To estimate the prevalence and factors associated with leisure-time physical inactivity in university students of a Physical Education course. Methodology: It is a cross-sectional study carried out in a public higher education institution from state of Bahia. The physical inactivity investigated by Prevalence Ratio (PR). Significance level was 5%. Results: 111 university students participated in it. The prevalence of physical inactivity in leisure-time was 14.4%. Female students were associated with leisure-time physical inactivity (PR: 6.22; CI95%: 1.62 - 23.90), university students of higher age groups were less inactive in leisure-time when compared to younger ones (PR: 0.18; 95%CI: 0.04 - 0.92), and married students were more inactive in leisure-time. Conclusion: The prevalence of physical inactivity in the leisure-time was lower in Physical Education students. Married female students aged between 18 to 20 years old had higher prevalence of leisure-time physical inactivity.
Keywords: Risk behavior; students; physical education; leisure activities